2022
DOI: 10.1097/mnm.0000000000001604
|View full text |Cite
|
Sign up to set email alerts
|

Correlation analysis of I-131 SPECT/CT uptake parameters with the success ablation treatment of thyroid remnant in patients with low-intermediate-risk differentiated thyroid cancer

Abstract: Objective To predict the successful outcome of radioactive iodine-131 (I-131) ablation treatment for differentiated thyroid cancer (DTC) patients using quantitative parameters from therapeutic I-131 SPECT/CT. Methods This retrospective study enrolled 145 DTC patients (41 males and 104 females) who had radioactive iodine-131 (I-131) (RAI) ablation therapy following thyroidectomy surgery from July 2020 to May 2021. The median age was 47 years (24-65 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…However, research on the quantitative parameters of SPECT/CT imaging 3 days after RAI adjuvant therapy has been relatively limited. Recently, studies have found that these parameters are associated with the efficacy of ablation therapy, and %ID was found to be a predictor of the successful outcome of ablation therapy in patients with DTC ( 6 ). Additionally, quantitative evaluation could serve as a predictive indicator for the disappearance of RAI accumulation in the thyroid bed after RAI adjuvant therapy ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, research on the quantitative parameters of SPECT/CT imaging 3 days after RAI adjuvant therapy has been relatively limited. Recently, studies have found that these parameters are associated with the efficacy of ablation therapy, and %ID was found to be a predictor of the successful outcome of ablation therapy in patients with DTC ( 6 ). Additionally, quantitative evaluation could serve as a predictive indicator for the disappearance of RAI accumulation in the thyroid bed after RAI adjuvant therapy ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…SPECT image reconstruction was performed by employing the ordered subset expectation maximization algorithm (OSEM) with 2 iterations and 10 subsets. Additional corrections, including scattering correction, sensitivity recovery, and attenuation correction based on CT data, were also performed ( 6 ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations